2015
DOI: 10.1007/s00415-015-7937-7
|View full text |Cite|
|
Sign up to set email alerts
|

A prospective study of the cumulative incidence and course of restless legs syndrome in de novo patients with Parkinson’s disease during chronic dopaminergic therapy

Abstract: The authors report the cumulative incidence of Restless Legs Syndrome (RLS) over a 3 years follow-up period in 92 de novo Parkinson's disease patients under chronic dopaminergic therapy and the clinical course of the sensory-motor disorder over 12 months as from its onset. The overall cumulative incidence of RLS was found by 15.3%, i.e. 14 incident cases, and by 11.9%, i.e. 11 incident cases, after the exclusion of possible "secondary" forms of the disorder. These figures are higher than those reported in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The increased incidence of RLS/WED in PD patients is supported by all three longitudinal studies ( 64 66 ), however the possible influence of dopaminergic therapy in inducing RLS/WED is reported in two out of three ( 64 , 65 ). Furthermore, neuroimaging showed a preserved dopaminergic pathway in PD+RLS/WED in comparison to PD alone.…”
Section: Longitudinal Studiesmentioning
confidence: 77%
See 1 more Smart Citation
“…The increased incidence of RLS/WED in PD patients is supported by all three longitudinal studies ( 64 66 ), however the possible influence of dopaminergic therapy in inducing RLS/WED is reported in two out of three ( 64 , 65 ). Furthermore, neuroimaging showed a preserved dopaminergic pathway in PD+RLS/WED in comparison to PD alone.…”
Section: Longitudinal Studiesmentioning
confidence: 77%
“…These findings suggest that dopaminergic medication may be crucial for the development of RLS/WED in PD patients. The same authors reported an updated cumulative incidence and clinical course study in the same cohort of patients after a 3-year follow-up ( 65 ). This study confirmed that RLS/WED prevalence is increased in PD patients under treatment in comparison to general population and drug naïve PD patients.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“… 43 Moreover, dopaminergic treatment of Parkinson's disease has been suggested to precipitate restless legs syndrome in some patients. 44 The risk locus on chromosome 15q23 (encompassing MAP2K5 and SKOR1 ) overlaps with GWAS signals of four different traits, including the posterior cortical atrophy variant of Alzheimer's disease ( appendix pp 39–41 ). The ORs of the shared SNP rs11637445 were 1·48 for posterior cortical atrophy and 0·89 for restless legs syndrome, which is consistent with the negative correlation between these two disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Lee and colleagues, in fact, stated that the duration of anti‐parkinsonian therapy is the most significant contributor to the development of RLS symptoms in the PD population (Lee, Shin, Kim, & Sohn, ), and a similar conclusion has been strongly suggested by Calzetti and colleagues (Calzetti, Angelini, Negrotti, Marchesi, & Goldoni, ). Moreover, some researchers have only analysed RLS in patients with PD, without any direct comparison with the general population (Bhalsing, Suresh, Muthane, & Pal, ; Braga‐Neto, da Silva‐Junior, Sueli Monte, de Bruin, & de Bruin, ; Gomez‐Esteban et al., ; Guerreiro, Nishikawa, Ferreira, Melo, & Prado, ; Lang & Johnson, ; Lee et al., ; Marchesi et al., , ; Neikrug et al., ; Ondo, Vuong, & Jankovic, ; Peralta et al., ; Svensson, Beiske, Loge, Beiske, & Sivertsen, ; Tan, Lum, & Wong, ; Verbaan, van Rooden, van Hilten, & Rijsman, ; Ylikoski, Martikainen, & Partinen, ); in other instances a case–control study had been performed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some researchers have only analysed RLS in patients with PD, without any direct comparison with the general population (Bhalsing, Suresh, Muthane, & Pal, 2013;Braga-Neto, da Silva-Junior, Sueli Monte, de Bruin, & de Bruin, 2004;Gomez-Esteban et al, 2007;Guerreiro, Nishikawa, Ferreira, Melo, & Prado, 2010;Lang & Johnson, 1987;Lee et al, 2009;Marchesi et al, 2016aMarchesi et al, , 2016bNeikrug et al, 2013;Ondo, Vuong, & Jankovic, 2002;Peralta et al, 2009;Svensson, Beiske, Loge, Beiske, & Sivertsen, 2012;Verbaan, van Rooden, van Hilten, & Rijsman, 2010;; in other instances a casecontrol study had been performed (Table 4).…”
Section: Restless Legs Syndrome and Periodic Leg Movementsmentioning
confidence: 99%